Vitamin K in human health and metabolism: A nutri-genomics review. (January 2022) - Rajagopal, Shalini; Gupta, Ayam; Parveen, Rabia; Shukla, Nidhi; Bhattacharya, Sanghati; Naravula, Jalaja; Kumar S, Anil; Mathur, Praveen; Simlot, Anita; Mehta, Sudhir; Bihari, Chhagan; Mehta, Sumita; et al.
Abstract: Background: Vitamins play an essential role in various physiological and biological processes, and their deficiency causes several health consequences in humans. Unlike vitamins A, B, C, D, E, the vitamin K (VK) deficiency is not dealt with profusely keeping in view of its inherent dietary sources and its health implications in human physiology such as blood coagulation. The VK family belongs to a variety of distinct subtypes in the length of side chains composed of isoprenoid families, and is important for various biological functions while much of the behaviour is not unknown. Scope and approach: In the recent past, a lot of knowledge has been derived from the VK deficiency and its comorbidities. This review emphasizes on the nutrigenomics perspective of VK deficiency as we throw light on diagnostic challenges of VK. Key findings and conclusions: We highlight the molecular physiological perspectives of VK using systems/nutri-genomics approaches and explore the human health effects of VK deficiency besides giving a gist of food-omics technologies. Highlights: Vitamins play a very important role in various physiological and biological processes. Amongst all vitamins, the vitamin K (VK) is not much deliberated and is involved in coagulation. With the advent of nutrigenomics based approaches, there arose an interest on the role of blood coagulation and genes, pathways associated with VK. The proteins associated with VK are largely regulated and involved in various diseases and co-morbidities. We highlight the essence of VK deficiency and discuss its inherent in nutrition and food-omics aspects.